Moderating Effect of Regulations on Organizational Factors and Construction Risk Management: A Proposed Framework - Adeleke, A. Q.; Bahaudin, A. Y.; Kamaruddeen, A. M. (International Journal of Economics and Financial Issues, 2016)
While certain organizational internal and external factors have been found to influence construction risk management among the construction companies. The influence of the organizational factors such as effective communication, team competency with skills, active leadership, political factor, organizational culture, technology factor and economic factor on construction risk management among the construction companies operating in Nigeria have not received considerable attention. This paper proposes regulations as the potential moderator on the relationship between organisational internal factors, external factors and construction risk management. Keywords: Organizational internal & external factors, Construction Risk management; Rules and Regulations JEL Classifications: G30, D80, L70